2019
DOI: 10.1002/ags3.12277
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of single‐site laparoscopic interval appendectomy for severe complicated appendicitis: Comparison to conventional emergency appendectomy

Abstract: Aim Single‐site laparoscopic interval appendectomy (SLIA) for severe complicated appendicitis after conservative treatment (CT) to ameliorate inflammation and eradicate the abscess should be safer and less invasive than emergency appendectomy (EA). However, only a few reports have been published regarding SLIA. Methods We retrospectively collected data on 264 consecutive patients admitted to Kinan Hospital for treatment of appendicitis between 2012 and 2018. The safety and feasibility of SLIA and its periopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…An alternative minimal invasive surgical method is single-incision laparoscopy, in which all instruments and the laparoscope are inserted through a multi-channel portal placed at the umbilicus [43]. Miyo et al study claims that Single-site laparoscopic interval appendectomy (SLIA) for severe complicated appendicitis after conservative treatment to restrict inflammation can be safe, feasible, and less invasive than appendicectomy and offers all the advantages of minimally invasive surgery despite its disadvantage of prolonging the hospital stay [44]. A 2017 systematic review showed that laparoscopic appendectomy, compared with open one, reduced the risk of surgical site infection, length of hospital stay, and time to oral intake without increasing the rate of intra-abdominal abscess [45].…”
Section: Therapymentioning
confidence: 99%
“…An alternative minimal invasive surgical method is single-incision laparoscopy, in which all instruments and the laparoscope are inserted through a multi-channel portal placed at the umbilicus [43]. Miyo et al study claims that Single-site laparoscopic interval appendectomy (SLIA) for severe complicated appendicitis after conservative treatment to restrict inflammation can be safe, feasible, and less invasive than appendicectomy and offers all the advantages of minimally invasive surgery despite its disadvantage of prolonging the hospital stay [44]. A 2017 systematic review showed that laparoscopic appendectomy, compared with open one, reduced the risk of surgical site infection, length of hospital stay, and time to oral intake without increasing the rate of intra-abdominal abscess [45].…”
Section: Therapymentioning
confidence: 99%
“…The treatment options for acute appendicitis have diversified to include antibiotic treatment, emergency surgery, and interval appendectomy, and the advantages and noninferiority of each treatment have been reported in previous studies 3,7–9 . WSES guideline which was published in 2020 recommended nonoperative treatment in the patients with uncomplicated acute appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment options for acute appendicitis have diversified to include antibiotic treatment, emergency surgery, and interval appendectomy, and the advantages and noninferiority of each treatment have been reported in previous studies. 3,[7][8][9] WSES guideline which was published in 2020 recommended nonoperative treatment in the patients with uncomplicated acute appendicitis. However, the success of the nonoperative approach requires careful patient selection and exclusion of patients with gangrenous acute appendicitis, abscesses, and diffuse peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…The probabilities of clinical improvement, recurrence, and complicated appendicitis with NOM were obtained from the Salminen et al [ 13 ]. The probabilities of selecting open or laparoscopic appendectomy or medical or surgical management of complicated appendicitis were obtained from observational studies [ 10 , 31 , 44 47 ].…”
Section: Methodsmentioning
confidence: 99%